Identification, Characterization and Evolutionary Patterns of Abiotic Stress Related Gene(s) in Moringa Oleifera - Saadat, Kashaf; Aftab, Beenish; Sadia, Sehrish; Akhtar, Sundus; Aftab, Mahwish (Journal of Basic and Emerging Sciences, 2024)
The drumstick tree (Moringa oleifera Lam.) is a perennial crop that has gained popularity in certain developing countries for its high-nutrition content and adaptability to arid and semi-arid environments. The genome of Moringa oleifera, a fast-growing Stress-tolerant orphan crop with highly valuable agronomical, nutritional and pharmaceutical properties, has recently been reported. The present study was conducted to study the seedling growth, morphological and molecular level changes of Moringa under saline soil conditions. Abiotic stress-related genes will be induced in Moringa oleifera and their response to different stress conditions are studied. Plants of Moringa oleifera will be collected. Extraction of DNA can be done by using the CTAB buffer method. PCR will be done for the amplification of abiotic stress-related genes. Bioinformatics analysis and phylogenetic analysis will be performed to check the genetic diversity of the abiotic stress-related gene in Moringa oleifera. The potential candidate of abiotic stress-related genes will be identified and characterized in M. oleifera including WARKY, MoTPS & MoTPP genes. The abiotic stress-responsive genes will also be investigated for genetic improvements. Our analysis reveals that members of the WARKY, TPPS and TPS genes family have an important role in the plant’s response to abiotic stress and are viable candidates for further characterization.